Environmental Horticulture Program Guide - Georgia Univ., Athens. Dept. of Vocational Education; Georgia Univ., Athens. Dept. of Vocational Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
This program guide contains the standard environmental horticulture curriculum for technical institutes in Georgia. The curriculum encompasses the minimum competencies required for entry-level workers in the environmental horticulture field. The general information section contains the following: purpose and objectives; program description, including admissions, typical job titles, and accreditation and certification; and curriculum model, including standard curriculum sequence and lists of courses. The next three sections contain the courses: general core courses (English, mathematics, interpersonal relations and professional development); fundamental technical courses (horticulture sciences, woody ornamental plant identification, herbaceous plant identification, greenhouse management I, horticulture construction, nursery production, landscape design, landscape installation, pest control); and specific technical courses (greenhouse management II, landscape management, garden center management, environmental horticulture internship). Each course consists of the following: a course overview (description, competency areas, prerequisites, credit hours, contact hours); course outline with student objectives and class and lab hours; and resource list. An appendix to the guide lists equipment needed for the program. (KC)
Sponsoring Agency: Georgia State Dept. of Technical and Adult Education, Atlanta.
Contract Number: GA-89-110013.
ERIC Note: For the program standards, see CE 062 126.
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Keywords: Behavioral Objectives; Competency Based Education; Course Content; Course Descriptions; Employment Potential; Entry Workers; Job Skills; Landscaping; Merchandising; Nurseries (Horticulture); Ornamental Horticulture; Plant Growth; Plant Identification; Plant Propagation; Postsecondary Education; Program Guides; State Curriculum Guides; Technical Education; Technical Institutes; Two Year Colleges; Georgia; Guides, Classroom -- Teacher